Gothic television - Wheatley, Helen (Helen M.); Manchester University Press (Manchester, UK : Manchester University Press, 2017)
Analysing key programmes - from 'Mystery and Imagination' and 'Dark Shadows' to 'The Woman in White' and 'Twin Peaks' - this text looks at the appearance of the gothic on television, uncovering an aspect of TV drama history which has remained critically unexplored.
This book is the first in-depth study of the Gothic on television. It defines and explores key instances of the genre across the history of television drama in the UK and US. The book builds a strong argument for the fact that the Gothic, in its various guises, is well-suited to television as a domestic medium.
Gothic television is the first full length study of the Gothic released on British and US television. An historical account, the book combines detailed archival research with analyses of key programmes, from Mystery and Imagination and Dark Shadows, to The Woman in White and Twin Peaks, and uncovers an aspect of television drama history which has, until now, remained critically unexplored. While some have seen television as too literal or homely a medium to successfully present Gothic fictions, Gothic television argues that the genre, in its many guises, is, and has always been, well-suited to television as a domestic medium, given the genre's obsessions with haunted houses and troubled families. This book will be of interest to lecturers and students across a number of disciplines including television studies, Gothic studies, and adaptation studies, as well as to the general reader with an interest in the Gothic, and in the history of television drama.
Introduction: Gothic television -- texts and contexts 1. Showing less, suggesting more: the ghost story on British television 2. Blood, guts and special effects: the heritage of horror on British television 3. The female Gothic: women, domesticity, and the Gothic adaptation 4. Keeping it in the family: American Gothic television in the 1960s 5. Televisuality and the new American Gothic Conclusion Teleography Filmography.
Includes filmography.
In English.
Description based on print record.
Available through ManchesterHive.
JSTOR
Keywords: Horror television programs -- Great Britain -- History and criticism; Horror television programs -- United States -- History and criticism; Émissions d'horreur télévisées -- Grande-Bretagne -- Histoire et critique; Émissions d'horreur télévisées -- États-Unis -- Histoire et critique; Popular Culture; SOCIAL SCIENCE / Popular Culture; PERFORMING ARTS / Television / History & Criticism; Horror television programs; Great Britain; United States; Criticism, interpretation, etc